Shorter specialist time intervals are associated with advanced stage on symptomatic oral cancer. (26th February 2018) - Seoane, J; Otero‐Rico, A; López‐Cedrún, JL; Varela‐Centelles, P
Abstract : Objectives: As longer times from the first symptom to diagnosis and treatment of oral cancers have been linked to poorer outcomes, this study investigates the contribution of the specialist to this time (STI). Subjects and Methods: A series of 228 oral/oropharyngeal squamous cell carcinoma patients were retrospectively studied to determine the STI and its related factors. Results: Patients were mostly males ( n  = 170; 74.5%), (50.7% stages I‐II), mean age = 61.4 ± 12.5 years. The STI median was 6 days (X± SD :6.8 ± 5.6 days). Time first symptom to diagnosis was 64 days (X± SD :91.0 ± 84.6 days). Univariate regression unveiled a significant association between STI and TNM stage, which was confirmed by multivariate regression. Conclusions: Specialist time interval is a short time interval in oral cancer diagnosis, imposing a limited time burden in the context of the whole interval until diagnosis. However, there seems to be room for improvement and a possible target for future interventions to shorten STI particularly for patients at early stages after their disease has been disclosed.